Factorization and inversion of finite and infinite comrade matrices. Issue 1 (22nd November 2019) - Tomeo, Venancio
Abstract : Motivated by current applications of the comrade matrices of large order, the infinite invertible comrade matrices are considered. These matrices are a generalization of the companion matrix and a particular case of the bordered tridiagonal matrices. A method based on a simple but suitable factorization is proposed for obtaining, in the finite‐dimensional case, a decomposition of the inverse. This procedure can be applied to infinite comrade matrices. Some illustrative examples are given.